Feasibility of custom strawberry farming in Oceanside California - Vargas, Ronald G. (Kansas State University, 2013)
The objective of this thesis is to determine if contract farming of fresh strawberries in Oceanside California is financially feasible. This is being considered as an alternative to managing the 185 acre fresh strawberry farm. The farming business is owned by a large fresh fruit marketing firm. As an independent custom grower I would not be subject to the same constraints as the marketing firm. No changes to management structure or product quality would be necessitated by this change. Assumptions for this study are specific to operating requirements for producing winter strawberries in North San Diego County in California. The cultural practices described and inputs used are considered to be usual for a well-managed commercial farm. The cost and returns are based upon actual historical data and representative of similar if not exact cultural practices and material inputs. The conceptual model used to guide the development of this study was taken from a generic feasibility study framework. It served as a controlled process to analyze the situation and determine the financial outcomes. The economic and financial viability analysis includes costs and returns per acre, monthly cash costs, sensitivity analysis, and overall profitability. The method used to assess the dimensions of viability was to weight them by evaluating key characteristics for relative strengths and weaknesses. The recommendation based upon this assessment is that the overall viability of the proposal is more than 80% and therefore merits the development of a comprehensive business plan.
Keywords: Custom farming; Business feasibility; Strawberry production; Farm management; Business (0310); Economics, Agricultural (0503); Horticulture (0471)